Pelatihan Implementasi Kurikulum Merdeka di SDN Mojoroto Jetis Mojokerto - Feriyanto Feriyanto; Rizky Oktaviana Eko Putri; Taswirul Afkar (LPPM Universitas Dharma Andalas, 2022)
The COVID-19 pandemic has a big impact on the education sector. The learning process is not optimal because it cannot be done directly, so learning is getting left behind (learning loss). As a result, the Ministry of Education and Culture issued a policy related to a Merdeka’ curriculum. The Merdeka’ curriculum is a curriculum that focuses on essential content so that students are able to explore and strengthen concepts. SD Negeri Mojoroto is one of the elementary schools located on the border of Jetis and Dawar Blandong sub-districts. Based on observations, Mojoroto Elementary School teachers still have difficulty understanding the independent curriculum. Because it is still considered new and there has been no socialization from any party. The implementation method is the preparation stage, implementation stage and evaluation stage. As for the results of this activity, the preparation stage resulted in the need for an introduction to an independent curriculum, preparation of materials and service instruments. At the implementation stage, presentations and questions and answers were held. While the evaluation stage resulted in a questionnaire response of participants in the good category. And suggestions in the form of increasing the duration of the training and video appearances as well as ice breaking to attract the attention of participants.